Sinopse e conservação das espécies de Melastomataceae do Parque Nacional do Iguaçu, Paraná – Brasil - Wink, Julia Gabriela (2022)
Melastomataceae is one of the main families of Angiosperms in Brazil, with 1,436 species, from which, 158 occur in the state of Paraná. Many of its species are pioneers and zoochoric, essential for regeneration andfloristic composition in the Atlantic Forest, which in turn is the phytogeographic domain covering the Iguaçu National Park. In this study we present the synopsis of Melastomataceae from the Iguaçu National Park. Two areas in the park were sampled from 2019 to February 2020, one covered with Seasonal Semideciduous Forest (SSF), and the Other in a transition between SSF na Mixed Ombrophilous Forest (MOF). In addition to these collections, they were analyzed on Specieslink and Jabot platforms, photos of samples deposited in the herbaries ASE, DVPR, EVB, HCF, HUCP, HUCS, HVC, IPA, IRAI, MBM, NY, RB, SHPR, UNOP, UPCB and US (acronyms according to Thiers, constantly updated). Seventeen species of Melastomataceae in four genera were found: Miconia (with 14 species), and Acisanthera, Chaetogastra and Pleroma (all with just one species). Seven species occur in the two vegetation types Iguaçu National Park (ParNa Iguaçu), while six occur only in MOF and four only in SSF. Out of the 17 species, five are endemic to Brazil, and six occur only in the south and southeast regions of the country. As for conservation status, all species found in the area are classified as Least Concern. This study registers nine new records for the ParNa Iguaçu. Furthermore, Miconia leaeichleri was collected for the first time in the area, which suggests the need for a greater collection effort in the western region of Paraná